Visibility region exploitation for phy authentication in xl-mimo systems - Demirci, Senanur; Afeef, Liza; Arslan, Hüseyin (My University, 2025)
Wireless networks are open to identity spoofing attacks because of their broadcast nature, emphasizing the need for strong security. Physical layer authentication (PLA) is a crucial strategy for securing wireless networks against such threats. Extra-large multiple-input multiple-output (XL-MIMO) technology, with its unique visibility region (VR) concept due to the near-field effect, offers a promising way to enhance network performance. This letter proposes a PLA approach using VR to create unique and robust signatures from the power and beamspace domain of XL-MIMO. Simulation results confirm the effectiveness of the proposed method in detecting attacks with high accuracy and low false alarm rates.
Keywords: Beamspace Domain; Extra-Large MIMO (XL-MIMO); Physical Layer Authentication (PLA); Spoofing Attack; Visibility Region (VR)